1990
DOI: 10.1099/0022-1317-71-3-531
|View full text |Cite
|
Sign up to set email alerts
|

Immunoaffinity purification and characterization of the envelope protein E1 of hog cholera virus

Abstract: The envelope protein E1 of hog cholera virus (HCV) was isolated by immunoaffinity purification with monoclonal antibodies (MAbs) directed against HCV. E1 consisted of a doublet of glycoproteins which varied in size from 51K to 56K between the three strains tested. E1 contains major antigenic determinants of HCV which are conserved, and are involved in neutralization by MAbs. In infected ceils, E 1 was found always connected with a glycoprotein of 31K. When Nlinked glycans were removed, E1 had a polypeptide bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Thus, the nine cysteines in the C-terminal half of E1 are not essential for the conformation and accessibility of epitopes on the Nterminal half of El. It has been shown that E1 forms homodimers as well as heterodimers with E3 (gp31) and that cysteines are involved in this dimerization process (Wensvoort et al, 1990;Thiel et al, 1991). Here, we showed that the N-terminally located cysteines are probably involved in the antigenic structure of El.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the nine cysteines in the C-terminal half of E1 are not essential for the conformation and accessibility of epitopes on the Nterminal half of El. It has been shown that E1 forms homodimers as well as heterodimers with E3 (gp31) and that cysteines are involved in this dimerization process (Wensvoort et al, 1990;Thiel et al, 1991). Here, we showed that the N-terminally located cysteines are probably involved in the antigenic structure of El.…”
Section: Discussionmentioning
confidence: 99%
“…The major antigenic protein of HCV is envelope glycoprotein E1 (Wensvoort et aL, 1990). The immune response against E1 alone is sufficient for protection, because vaccination with a recombinant pseudorabies virus (PRV) which expresses the E1 gene of HCV strain Brescia protects swine against hog cholera (van Zijl et aL, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The nomenclature of the pestivirus proteins used in this report will be proposed to the International Committee on Taxonomy of Viruses by the Flaviviridae Study Group. The nomenclature of the pestivirus envelope proteins used by the CSFV research group in Lelystad in previous publications (Hulst et al, 1993(Hulst et al, , 1994Moormann et al, 1990 ;van Zijl et al, 1991 ;Wensvoort, 1989 ;Wensvoort et al, 1986Wensvoort et al, a, b, 1990 …”
Section: Detection Of Ementioning
confidence: 99%
“…Although all three glycoproteins are associated with the virus envelope , up to now only antibodies against the two largest glycoproteins have been detected in animals infected with pestiviruses (Kwang et al, 1992 ;Terpstra & Wensvoort, 1988). The most immunodominant protein present in the virus envelope of pestiviruses is E2 (Donis & Dubovi, 1987 ;Wensvoort et al, 1990). When E2 is used as a subunit vaccine, it elicits high levels of neutralizing antibodies and protects pigs from classical swine fever (Hulst et al, 1993 ;van Zijl et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The surface structure of pestivirus virions is composed of three glycoproteins, E rns , E1, and E2 (46). E2 is present as a homodimer and as an E2-E1 heterodimer (46,51). The amino acid C terminus of E2 (and probably of E1 as well) functions as a membrane-spanning domain (14) and anchors these E2-E1 and E2-E2 dimers in the viral lipid membrane.…”
mentioning
confidence: 99%